The development of complex tooth shape in reptiles - Zahradnicek, Oldrich; Buchtova, Marcela; Dosedelova, Hana; Tucker, Abigail S. (Frontiers in Physiology, 2014)
Reptiles have a diverse array of tooth shapes, from simple unicuspid to complex multicuspid teeth, reflecting functional adaptation to a variety of diets and eating styles. In addition to cusps, often complex longitudinal labial and lingual enamel crests are widespread and contribute to the final shape of reptile teeth. The simplest shaped unicuspid teeth have been found in piscivorous or carnivorous ancestors of recent diapsid reptiles and they are also present in some extant carnivores such as crocodiles and snakes. However, the ancestral tooth shape for squamate reptiles is thought to be bicuspid, indicating an insectivorous diet. The development of bicuspid teeth in lizards has recently been published, indicating that the mechanisms used to create cusps and crests are very distinct from those that shape cusps in mammals. Here, we introduce the large variety of tooth shapes found in lizards and compare the morphology and development of bicuspid, tricuspid and pentacuspid teeth, with the aim of understanding how such tooth shapes are generated. Next, we discuss whether the processes used to form such morphologies are conserved between divergent lizards and whether the underlying mechanisms share similarities with those of mammals. In particular, we will focus on the complex teeth of the chameleon, gecko, varanus and anole lizards using SEM and histology to compare the tooth crown morphology and embryonic development.